2014
DOI: 10.1186/1476-069x-13-112
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and lung function related to ultrafine and fine particles exposure assessed by personal and indoor monitoring: a cross-sectional study

Abstract: BackgroundExposure to ambient air particulate matter (PM) has been linked to decline in pulmonary function and cardiovascular events possibly through inflammation. Little is known about individual exposure to ultrafine particles (UFP) inside and outside modern homes and associated health-related effects.MethodsAssociations between vascular and lung function, inflammation markers and exposure in terms of particle number concentration (PNC; d = 10-300 nm) were studied in a cross-sectional design with personal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Two studies from Denmark demonstrated that exposure to UFP away from home was significantly inversely correlated with microvascular function and positively associated with systemic inflammation. 6, 8 There was no association between these changes and PM 10 and PM 2.5 . Decreased lung function, i.e.…”
Section: The Impact Of Ambient Ufp and Np On Human Healthmentioning
confidence: 84%
See 1 more Smart Citation
“…Two studies from Denmark demonstrated that exposure to UFP away from home was significantly inversely correlated with microvascular function and positively associated with systemic inflammation. 6, 8 There was no association between these changes and PM 10 and PM 2.5 . Decreased lung function, i.e.…”
Section: The Impact Of Ambient Ufp and Np On Human Healthmentioning
confidence: 84%
“…forced expired volume in 1 sec (FEV1) and forced vital capacity, and elevated type 2 diabetes marker (HbA1c) were associated with the level of indoor UFP, but not PM 2.5 . 6, 8 A recently published 6-year (2001–2007) cohort study including more than 100,000 women in California reported that the mortality caused by ischemic heart disease (IHD) was significantly associated with UFP, their contents of EC and metals, and mobile source. Although similar association was also found between IHD mortality and PM 2.5 , statistical analysis showed that UFP mass and its constituents had a better fit and a lower p-value than those of PM 2.5 .…”
Section: The Impact Of Ambient Ufp and Np On Human Healthmentioning
confidence: 99%
“…Exposure to ultrafine particles causes chronic inflammatory responses, accompanied by cytokines and chemokine release (Seagrave, 2008). Particles greater than 10 μm are filtered in the nose and upper airway, while smaller particle sizes are inhaled into the lungs, which filter out the ultrafine particles through the actions of eosinocyte, neutrophils, and macrophages (Olsen et al, 2014). In addition, ultrafine particles cause sinusitis, bronchitis, asthma, and lung cancer, as well as chronic bronchitis (McConnell et al, 2003).…”
Section: Health Effect Of the Ultrafine Particles Formed By Chemical mentioning
confidence: 99%
“…The nanoTracer has been compared to other instruments in the laboratory [69, 70]. It has been used to evaluate determinants of ultrafine particle concentrations in homes [71] and to investigate possible associations among ultrafine particle exposures and adverse cardiopulmonary health [7274]. …”
Section: Beyond Pm Massmentioning
confidence: 99%